INNOVATIVE METHODS OF TEACHING A FOREIGN LANGUAGE AT A TECHNICAL UNIVERSITY - Askarova G.X (Лучшие интеллектуальные исследования, 2024)
Abstract. The question of improving the effectiveness of teaching is one of the oldest in the history of mankind. The search for optimal forms and methods is inextricably linked with the development of innovative technologies, which at some point can be of decisive importance. Over the past 15 years, with the advent of new information technologies, the Internet, mobile phones, tablets, there have been changes in how users integrate these achievements into their personal lives. Changes in the technological sphere not only found their reflection in the educational sector, but also had and continue to have a direct impact on the processes taking place in it. The article describes the forms of innovative teaching of a foreign language with and without information and communication technologies, including online conferences, building a virtual environment, computer programs, etc. The authors of the article believe that with the use of innovative methods, foreign language communication of students acquires a new modern content. In conclusion, the invaluable importance of educational networks, both local and global, is noted; the enormous potential of using innovative methods in the field of teaching foreign languages is emphasized.